2017
DOI: 10.1186/s12889-017-4782-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of package inserts of local and imported antihypertensive medications in Palestine

Abstract: BackgroundPackage inserts (PIs) as a reliable reference for patients and health care providers should provide accurate, complete and up-to-date information. The purpose of the current study is to assess and compare the PIs of antihypertensive agents locally produced in Palestine and their imported counterparts.MethodsThirty-five PIs were assessed for the presence of 31 information statements using a scoring method. Word counting of 20 headings and subheadings was used to evaluate and compare local and imported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 42 publications
3
20
0
Order By: Relevance
“…Inadequate information in PPIs has been the scope for many studies around the world. A Palestinian study carried out 2017 comparing the PPIs of local and imported anti-hypertensive drugs concluded similar findings regarding adverse drug reaction, date of last revision, and inactive ingredients [17]. Another study conducted in Southern India indicated that the information mentioned in the analysed inserts were not sufficient to ensure safe drug utilisation, and it recommended to review current PPIs based on scientific guidelines [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inadequate information in PPIs has been the scope for many studies around the world. A Palestinian study carried out 2017 comparing the PPIs of local and imported anti-hypertensive drugs concluded similar findings regarding adverse drug reaction, date of last revision, and inactive ingredients [17]. Another study conducted in Southern India indicated that the information mentioned in the analysed inserts were not sufficient to ensure safe drug utilisation, and it recommended to review current PPIs based on scientific guidelines [16].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of any of the previously mentioned statements in either PPI was scored as one and its absence as zero, and then the calculation of total score for all anti-diabetic agents was done. Another method was used to evaluate PPIs by applying simple word counting of the major headings [11, 12, 1719], which is an important method for evaluation of PPIs. Therefore, 17 heading and subheadings of both local and imported PPIs were evaluated for the quantity of information by using simple word counting.…”
Section: Methodsmentioning
confidence: 99%
“…The Palestinian Ministry of Health (MOH) requires that medication inserts be bilingual, in both Arabic and English, but does not give any recommendations about specific DIL designs, the quality of information or length of text [17–19]. It was noted that DILs of Palestinian-marketed medications contained incomplete and limited information compared with their counterparts marketed in other countries [5, 2022]. Although some research has been done of the DILs of medications available in Palestine [5, 20], no study compared the the information provided by local and imported NSAIDS.…”
Section: Introductionmentioning
confidence: 99%
“…It was noted that DILs of Palestinian-marketed medications contained incomplete and limited information compared with their counterparts marketed in other countries [5, 2022]. Although some research has been done of the DILs of medications available in Palestine [5, 20], no study compared the the information provided by local and imported NSAIDS. The reasons that NSAIDs were selected in this study is that they are among the most commonly dispensed medications in the Palestinian pharmacies, and these medications are usually dispensed as self-medications or sold over-the-counter (OTC) [23–25].…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings regarding the superiority of information in both the quality and quantity of imported over local medications were found in a recent study in Palestine. [23]…”
Section: Discussionmentioning
confidence: 99%